The Potential of Game-based Micro-learning Resources for Engaging Learners with Intercultural Competence Development - Sylvester, Arnab; Ludmila, Walaszcyk (UNIMAS Publisher, 2022)
This article discusses the potential of the application of interactive micro-learning content that aims to develop intercultural competences in the workplace, focusing on the pedagogically-informed design of playful interactive learning resources for engaging learners with topics related to cultural risks. Eight topics were identified through our engagement with 154 personnel from multicultural organisations across five European countries, including cross-cultural awareness, stereotypes, and communication. A competence map was then developed, articulating the specific aspects of these topics, which informed online content development. Findings from the evaluation of the online educational materials across the five countries (n=223 participants) suggest the significance and relevance of the topics in the workplace and the value of using playful micro-resources for delivering topics that were deemed less attractive.